A new extension of odd half-Cauchy Family of distributions: Properties and applications with regression modeling - Subrata Chakraburty; Morad Alizadeh; Laba Handique; Emrah Altun; G. G. Hamedani (Statistics in Transition New Series, 2021)
The paper proposes a new family of continuous distributions called the extended odd half Cauchy-G. It is based on the T − X construction of Alzaatreh et al. (2013) by consider ing half Cauchy distribution for T and the exponentiated G(x;ξ) as the distribution of X. Several particular cases are outlined and a number of important statistical characteristics of this family are investigated. Parameter estimation via several methods, including maximum likelihood, is discussed and followed up with simulation experiments aiming to asses their performances. Real life applications of modeling two data sets are presented to demonstrate the advantage of the proposed family of distributions over selected existing ones. Finally, a new regression model is proposed and its application in modeling data in the presence of covariates is presented
Keywords: 519; T-X method; regression; simulation; estimation